The quinoline framework and related scaffolds in natural products with anti-Leishmania properties - Gloria Yaluff; Gloria Yaluff; Leídi Herrera; Leídi Herrera; Miriam Soledad Rolón; Celeste Vega; Hugo Cerecetto; Hugo Cerecetto (Frontiers in Chemistry)
For almost one hundred years, the quinoline heterocycle has been recognized as a privileged pharmacophore in anti-Leishmania agents. Early on, the action of compounds with this scaffold, found in some natural alkaloids, was tested against different Leishmania stages and strains. Different structural arrangements containing the quinoline framework have been described in different in vitro and in vivo anti-Leishmania alkaloids, namely, quinoline proper, isoquinoline, and quinolone, among others. In recent years, new quinoline derivatives isolated from nature have been described, in addition to having carried out in-depth in vitro and in vivo biological studies, as well as chemical modifications to obtain new leaders. This review updates the state of the art on naturally occurring quinolines and some synthetic derivatives to provide therapeutic tools and strategies to explore new drugs based on this chemosystem for the treatment of leishmaniasis.